Synergies or Trade-Offs? Optimizing a Virtual Urban Region to Foster Plant Species Richness, Climate Regulation, and Compactness Under Varying Landscape Composition - Schwarz, Nina; Hoffmann, Falk; Knapp, Sonja; Strauch, Michael (Frontiers in Environmental Science, 2020)
Ongoing urbanization forces us to reflect on how we can cater for multiple targets when building cities. In this study, we investigate whether compactness as a common urban development strategy, climate regulation as an example for an ecosystem service, and vascular plant species richness as a measure of biodiversity form a synergistic relationship or whether trade-offs exist. We use a genetic algorithm to optimize the spatial allocation of three types of land cover blocks in a stylized urban region. These blocks are categorized as high-density, low-density, or park blocks, depending on the proportion of green and built-up cells within each block. We systematically vary landscape composition at the block level, but keep city size constant. Our most important finding is that the relationships of target functions can shift between trade-off and synergy, and this is shaped by landscape composition. For example, we found a trade-off between species richness and urban compactness in landscapes with large proportions of high-density areas and parks, while they have a synergistic relationship in low-density landscapes. Such dependencies of trade-offs and synergies on landscape composition need to be explored further, which may help address the wickedness of urban planning problems.